Empirical Verification of the Control System Model of Profit Rate - Park, Seong Jin (International Journal of Control, Automation and Systems, 2024)
This note aims to empirically verify the control system model of profit rate established by Park and Yang [4]. Specifically, it is shown that the real profit rate has gradually fallen in 8 countries over the last several decades. Then, using the parameters estimated from the real data, the simulated profit rates are obtained from the control system model, and compared with the real profit rates. As a result, this note shows that although the short-run behaviors are different, the control system model well captures the long-run decline in profit rate for all countries.
Keywords: Control system models; Feedback control system; Longest run; Parameters estimated; Profit rate; Short runs; Economics; feedback control system; profit rate